IDENTIFICATION OF FACTORS IN SELECTING HIGH SCHOOL USING FACTOR ANALYSIS - Suciptawati, Ni Luh Putu; Jayanegara, Ketut (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
Parents want the best education for their children. Before starting the academic year, parents focus on finding the most suitable schools for their children. This study aimed to examine the factors affecting parents’ decision-making when selecting schools. A sample of 150 parents whose children are incoming high school students in 2020/2021 is involved in this study and selected using a snowball sampling technique and confirmatory factor analysis. This study has shown that the quality of the teachers is the factor that parents consider the most in their decision-making process. It is followed by the tuition and fee costs, the school facilities, and the school achievements.